Curable composition
Patent Information
- Application Number
- KR1020200107068
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-25
- Publication Date
- 2026-09-02
- Estimated Expiration
- 2040-08-25
Smart Images

Figure 112020089353824-PAT00011_ABST
Abstract
Description
Technology Field
[0001] This application relates to a curable composition and a battery module. Background Technology
[0002] Batteries can be broadly classified into primary and secondary batteries. Secondary batteries, also known as rechargeable batteries, can be repeatedly charged and used. Examples of secondary batteries include nickel-cadmium batteries, nickel-metal hybrid batteries, nickel-hydrogen batteries, or lithium secondary batteries.
[0003] These secondary batteries have emerged as a major energy storage technology and are being applied or researched for application in various fields, including home appliances, industry, transportation, and power storage.
[0004] Depending on the application, there are cases where a so-called battery module is configured using multiple unit battery cells, or a so-called battery pack is configured using multiple battery modules.
[0005] For example, when a secondary battery is used as a power source for so-called electric vehicles such as electric propulsion vehicles, hybrid electric vehicles (HEV), battery electric vehicles (BEV), or plug-in hybrid electric vehicles (PHEV), a battery module or battery pack is configured using multiple unit battery cells to meet the required power and capacity requirements.
[0006] In battery modules or battery packs, multiple unit battery cells are located relatively close to each other. Therefore, heat or fire generated in any one or part of a battery cell inside a battery module or battery pack can easily affect other adjacent battery cells and, in some cases, may cause chain ignition. The problem to be solved
[0007] The present application provides a curable composition, and in one example, said curable composition may be used as a potting material when constructing a battery module or battery pack. The potting material may be a material that covers and contacts at least some or all of a plurality of unit battery cells within a battery module or battery pack. The present application provides a curable composition that possesses excellent thermal insulation and heat shielding properties and exhibits resistance to flame, thereby controlling the heat generated in the battery cells of the battery module or pack and preventing chain ignition, etc., when applied as a potting material. The present application also provides a curable composition that has excellent potting efficiency by controlling viscosity or thixotropy to an appropriate level before curing, and forms a stable potting structure without the generation of unnecessary bubbles after curing. The present application provides a curable composition that exhibits low density after curing, thereby providing a high-output battery module or pack that is lightweight relative to its volume. The present application also provides a curable composition that has excellent required physical properties, including insulation properties. means of solving the problem
[0008] Among the physical properties mentioned in this specification, if the measurement temperature affects the property, the property is the property measured at room temperature unless specifically otherwise stipulated.
[0009] In this specification, the term "room temperature" refers to a temperature in a state that is not specifically heated or cooled, and may mean any temperature within the range of about 10°C to 30°C, for example, about 15°C or higher, 18°C or higher, 20°C or higher, or about 23°C or higher and about 27°C or lower. Additionally, unless specifically otherwise specified, the unit of temperature referred to in this specification is °C.
[0010] In this specification, the term monovalent hydrocarbon group may mean a monovalent residue derived from a compound composed of carbon and hydrogen or a derivative thereof, unless specifically otherwise defined. For example, a monovalent hydrocarbon group may comprise 1 to 25 carbon atoms. Examples of monovalent hydrocarbon groups may include alkyl groups, alkenyl groups, alkynyl groups, or aryl groups.
[0011] In this specification, the term alkyl group or alkoxy group may mean an alkyl group or alkoxy group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms, unless specifically otherwise defined. The alkyl group or alkoxy group may be straight-chain, branched-chain, or cyclic. The alkyl group or alkoxy group may optionally be substituted with one or more substituents.
[0012] In this specification, the term alkenyl group or alkynyl group may mean an alkenyl group or alkynyl group having 2 to 20 carbon atoms, 2 to 16 carbon atoms, 2 to 12 carbon atoms, 2 to 8 carbon atoms, or 2 to 4 carbon atoms, unless specifically otherwise defined. The alkenyl group or alkynyl group may be linear, branched, or cyclic, and may optionally be substituted with one or more substituents.
[0013] In this specification, the term "aryl group" may refer to a monovalent residue derived from a compound or its derivative comprising a structure in which a benzene ring or two or more benzene rings are connected, or in which one or more carbon atoms are condensed or bonded while sharing. The scope of "aryl group" as used in this specification may include not only functional groups commonly referred to as aryl groups, but also so-called aralkyl groups or arylalkyl groups. An aryl group may be, for example, an aryl group having 6 to 25 carbon atoms, 6 to 21 carbon atoms, 6 to 18 carbon atoms, or 6 to 12 carbon atoms. Examples of aryl groups may include a phenyl group, dichlorophenyl, chlorophenyl, phenylethyl group, phenylpropyl group, benzyl group, tolyl group, xylyl group, or naphthyl group.
[0014] Examples of substituents that may optionally substitute on an alkoxy group or a monovalent hydrocarbon group in this specification include, but are not limited to, halogens such as chlorine or fluorine, epoxy groups such as glycidyl groups, epoxyalkyl groups, glycidoxyalkyl groups or alicyclic epoxy groups, acryloyl groups, methacryloyl groups, isocyanate groups, thiol groups, or monovalent hydrocarbon groups.
[0015] The curable composition of the present application may include a polyorganosiloxane component comprising a curable polyorganosiloxane. In this specification, a polyorganosiloxane component comprising a specific polyorganosiloxane may refer to the product of a polymerization for forming said specific polyorganosiloxane.
[0016] The above-mentioned curable polyorganosiloxane can be represented by the following chemical formula 1 in one example.
[0017] [Chemical Formula 1]
[0018]
[0019] In Chemical Formula 1, R1 is independently an alkyl group, an alkenyl group, an aryl group, or an alkyl halide group, R2 is a hydroxyl group, an alkoxy group, an alkenyl group, or an alkynyl group, and m is a number in the range of 10 to 350.
[0020] The polyorganosiloxane component containing the polyorganosiloxane of Chemical Formula 1 may be called the first polyorganosiloxane component to distinguish it from the polyorganosiloxane component that is the curing agent component when the polyorganosiloxane component is also applied as the curing agent component described later.
[0021] The above polyorganosiloxane component may be a product of a polymerization reaction to form the polyorganosiloxane of the above chemical formula 1, and thus may be a component containing the same.
[0022] In one example, the first polyorganosiloxane component may have an average unit corresponding to the curable polyorganosiloxane of Formula 1.
[0023] The term "average unit" refers to a unit representing the average number of moles of each siloxane unit present in the polyorganosiloxane component, calculated by converting the sum of the moles of all siloxane units present in the polyorganosiloxane component to 1. The siloxane unit includes the chemical formula (R3SiO2), referred to as the so-called M unit. 1 / 2 The unit of ), the chemical formula (R2SiO2) called the so-called D unit 2 / 2 The unit of ), the chemical formula (RSiO₂) called the so-called T unit 3 / 2 The chemical formula (SiO₂) referred to as the unit of ) and the so-called Q unit 4 / 2 There is a unit of ). In each of the above siloxane units, R is an organic functional group bonded to a silicon atom, and may be, for example, a monovalent hydrocarbon group, an alkoxy group, or a hydrogen atom.
[0024] In one example, the above polyorganosiloxane component may have an average unit of the following chemical formula 1-1.
[0025] [Chemical Formula 1-1]
[0026] (R1(R2)2SiO 1 / 2 ) 2 / (2+m) ((R1)2SiO 2 / 2 ) m / (2+m)
[0027] In Chemical Formula 1-1, R1 and R2 are organic functional groups bonded to the silicon atoms of each siloxane unit, specifically R1 and R2 of Chemical Formula 1, respectively, and m is a number in the range of 10 to 350.
[0028] The above polyorganosiloxane component may have a viscosity of 20,000 mPa·s or less at 25°C. The viscosity referred to in this specification is the viscosity measured with a Brookfield LV type viscometer as in the measurement method of the example described below, and is the viscosity measured under conditions of spindle #63 (or #64) and rpm 10. The above viscosity is 50 mPa·s or more, 60 mPa·s or more, 70 mPa·s or more, 80 mPa·s or more, 90 mPa·s or more, 100 mPa·s or more, 150 mPa·s or more, 200 mPa·s or more, 250 mPa·s or more, 300 mPa·s or more, 350 mPa·s or more, 400 mPa·s or more, 450 mPa·s or more, 700 mPa·s or more, 750 mPa·s or more, 600 mPa·s or more, 650 mPa·s or more, 700 mPa·s or more, 750 mPa·s or more, 800 mPa·s or more, 850 mPa·s or more, 900 mPa·s or more, 950 mPa·s or more, 1000 mPa·s or more, in other examples 1100 mPa·s or more, 1200 mPa·s or more, 1300 mPa·s or more, 1400 mPa·s or more, 1500 mPa·s or more, 1600 mPa·s or more, 1700 mPa·s or more, 1800 mPa·s or more, 1900 mPa·s or more, or 2000 mPa·s or more, or 15000 mPa·s or less, 10000 mPa·s or less, 9000 mPa·s or less, 8000 mPa·s or less, 7000 mPa·s or less, 6000 mPa·s or less, 5000 mPa·s or less, 4900 mPa·s or less, 4800 mPa·s or less, 4700 mPa·s or less, 4600 mPa·s or less, 4500 mPa·s or less, 4400mPa·s or less, 4300mPa·s or less, 4200mPa·s or less, 4100mPa·s or less, 4000mPa·s or less, 3900mPa·s or less, 3800mPa·s or less, 3700mPa·s or less, 3600mPa·s or less, 3500mPa·s or less, 3400mPa·s or less, 3300mPa·s or less, 3200mPa·s or less,3100 mPa·s or less, 3000 mPa·s or less, 2900 mPa·s or less, 2800 mPa·s or less, 2700 mPa·s or less, 2600 mPa·s or less, 2500 mPa·s or less, 2400 mPa·s or less, 2300 mPa·s or less, 2200 mPa·s or less, 2100 mPa·s or less, 2000 mPa·s or less, 1900 mPa·s or less, 1800 mPa·s or less, 1700 mPa·s or less, 1600 mPa·s or less, 1500 mPa·s or less, 1400 mPa·s or less, 1300 mPa·s or less, 1200 mPa·s or less, 1100 mPa·s or less, 1000 mPa·s or less, It may be 950 mPa·s or less, 900 mPa·s or less, 850 mPa·s or less, 800 mPa·s or less, 750 mPa·s or less, 700 mPa·s or less, 650 mPa·s or less, 600 mPa·s or less, 750 mPa·s or less, 700 mPa·s or less, 450 mPa·s or less, 400 mPa·s or less, 350 mPa·s or less, 300 mPa·s or less, 250 mPa·s or less, or 200 mPa·s or less.
[0029] A curable composition exhibiting physical properties suitable for the purpose of the present application can be provided by including the above-mentioned polyorganosiloxane or by applying a polyorganosiloxane component having the above-mentioned average unit and exhibiting the above-mentioned viscosity.
[0030] In one example, the above polyorganosiloxane component may be a condensation curing type or an addition curing type. In the case of a condensation curing type, R1 in Formula 1 or 1-1 may be a hydroxyl group or an alkoxy group, and in the case of an addition curing type, R1 in Formula 1 or 1-1 may be an alkenyl group or an alkynyl group.
[0031] The proportion of the polyorganosiloxane component in the curable composition may be controlled according to the purpose, but in terms of providing a curable composition with suitable physical properties, the proportion may be in the range of about 39 to 95 weight%. The proportion is the proportion in the curable composition excluding the weight of the solvent if the curable composition contains a solvent. The above ratio is 41 wt% or more, 43 wt% or more, 45 wt% or more, 47 wt% or more, 49 wt% or more, 51 wt% or more, 53 wt% or more, 55 wt% or more, 57 wt% or more, 59 wt% or more, 61 wt% or more, 63 wt% or more, 65 wt% or more, 67 wt% or more, 69 wt% or more, 71 wt% or more, 73 wt% or more, 75 wt% or more, 77 wt% or more, 79 wt% or more, 81 wt% or more, 83 wt% or more, 85 wt% or more, 87 wt% or more, or 89 wt% or more, or 93 wt% or less, 91 wt% or less, 89 wt% or less, 87 wt% or less, 85 wt% or less, 83 wt% or less, 81 wt% or less, 79 wt% or less, 77 wt% or less, It may be 75% by weight or less, 73% by weight or less, 71% by weight or less, 69% by weight or less, 67% by weight or less, 65% by weight or less, 63% by weight or less, 61% by weight or less, or 59% by weight or less.
[0032] In other examples, the proportion of the polyorganosiloxane component based on the total weight of the curable composition (excluding the weight of the solvent if it contains a solvent) excluding the filler described below may be in the range of 80 to 99 weight%. In other examples, the proportion may be 82 weight% or more, 84 weight% or more, 86 weight% or more, 88 weight% or more, 90 weight% or more, 92 weight% or more, or 94 weight% or more, or 97 weight% or less, 95 weight% or less, 93 weight% or less, or 91 weight% or less.
[0033] The curable composition may include a filler together with the polyorganosiloxane component. In one example, a hollow filler may be used as the filler. Such a filler is included to adjust properties such as viscosity and thixotropy of the curable composition to suit the purpose, and the cured product of the curable composition may have the desired thermal insulation, heat shielding, and resistance to flame.
[0034] Fillers having a predetermined particle size and / or density may be used. By controlling such particle size and / or density, the dispersibility of the filler within the curable composition can be controlled, and the dispersed filler can control physical properties such as viscosity and / or thixotropy of the composition. Furthermore, fillers with such particle size and / or density are advantageous for securing desired lightness, heat insulation, thermal insulation, and resistance to flame.
[0035] For example, the above filler may have a D50 particle size within the range of 10 μm to 100 μm. The D50 particle size is a diameter also referred to as the so-called median diameter, and is a particle size measured according to the method of the example described below. The above D50 particle size is 12 μm or more, 14 μm or more, 16 μm or more, 18 μm or more, 20 μm or more, 22 μm or more, 24 μm or more, 26 μm or more, 28 μm or more, 30 μm or more, 32 μm or more, 34 μm or more, 36 μm or more, 38 μm or more, 40 μm or more, 42 μm or more, 44 μm or more, 46 μm or more, 48 μm or more, 50 μm or more, 52 μm or more, 54 μm or more, 56 μm or more, or 58 μm or more, or 98 μm or less, 96 μm or less, 94 μm or less, 92 μm or less, 90 μm or less, 88 μm or less, 86 μm or less, 84 μm or less, 82 μm or less, 80 It may be μm or less, 78 μm or less, 76 μm or less, 74 μm or less, 72 μm or less, 70 μm or less, 68 μm or less, 66 μm or less, 64 μm or less, 62 μm or less, or about 60 μm or less.
[0036] The above filler may have a density in the range of about 0.05 to 1 g / ml. The above density is, in other examples, 0.01 g / ml or more, 0.15 g / ml or more, 0.2 g / ml or more, 0.25 g / ml or more, 0.3 g / ml or more, 0.35 g / ml or more, 0.4 g / ml or more, 0.45 g / ml or more, 0.5 g / ml or more, 0.55 g / ml or more, or 0.6 g / ml or more, or 0.95 g / ml or less, 0.9 g / ml or less, 0.85 g / ml or less, 0.8 g / ml or less, 0.75 g / ml or less, 0.7 g / ml or less, 0.65 g / ml or less, 0.6 g / ml or less, 0.55 g / ml or less, 0.5 g / ml or less, 0.45 g / ml or less, 0.4 g / ml or less, 0.35 g / ml or less, 0.3 g / ml or less, It may be 0.25 g / ml or less, 0.2 g / ml or less, or about 0.15 g / ml or less.
[0037] As for the filler, various types may be applied without special limitations as long as they have the particle size and / or density as described above and can be uniformly mixed with the polyorganosiloxane component.
[0038] For example, known organic fillers, inorganic fillers, or organic-inorganic mixed fillers may be used as fillers. Even when hollow fillers are applied, organic particles in which the shell portion is made of organic material, inorganic particles in which it is made of inorganic material, and / or organic-inorganic particles made of organic-inorganic material may be used. Examples of such particles include acrylic particles such as PMMA (poly(methyl methacrylate)), epoxy particles, nylon particles, styrene particles and / or copolymer particles of styrene / vinyl monomers, and inorganic particles such as silica particles, alumina particles, indium oxide particles, tin oxide particles, zirconium oxide particles, zinc oxide particles and / or titania particles, but are not limited thereto.
[0039] In one example, the hollow filler may be a particle in which the shell portion is made of soda-lime material (soda-lime filler), a particle in which the shell portion is made of soda-lime borosilicate material (soda-lime borosilicate filler), a cenosphere filler, or other silica particles.
[0040] The above filler may be included in a ratio of 3 to 150 parts by weight relative to 100 parts by weight of the polyorganosiloxane component. The above ratios in other examples are 5 parts by weight or more, 7 parts by weight or more, 9 parts by weight or more, 11 parts by weight or more, 13 parts by weight or more, 15 parts by weight or more, 17 parts by weight or more, 19 parts by weight or more, 21 parts by weight or more, 23 parts by weight or more, 25 parts by weight or more, 27 parts by weight or more, 29 parts by weight or more, 31 parts by weight or more, 33 parts by weight or more, 35 parts by weight or more, 37 parts by weight or more, 39 parts by weight or more, 41 parts by weight or more, 43 parts by weight or more, 45 parts by weight or more, 47 parts by weight or more, 49 parts by weight or more, 51 parts by weight or more, 53 parts by weight or more, 55 parts by weight or more, 57 parts by weight or more, 59 parts by weight or more, 61 parts by weight or more, 63 parts by weight or more, 65 parts by weight or more, 67 parts by weight or more, 69 parts by weight or more, 71 parts by weight or more, 73 parts by weight It may be 75 parts by weight or more, 77 parts by weight or more, 79 parts by weight or more, 81 parts by weight or more, 83 parts by weight or more, 85 parts by weight or more, 87 parts by weight or more, or 89 parts by weight or more, or 145 parts by weight or less, 140 parts by weight or less, 135 parts by weight or less, 130 parts by weight or less, 125 parts by weight or less, 120 parts by weight or less, 115 parts by weight or less, 110 parts by weight or less, 105 parts by weight or less, 100 parts by weight or less, 98 parts by weight or less, 96 parts by weight or less, 94 parts by weight or less, 92 parts by weight or less, or about 90 parts by weight or less.
[0041] Within the above range, the dispersibility of the filler within the curable composition is controlled, physical properties such as viscosity and / or thixotropy of the composition are stably maintained at the target level, and the desired lightweightness, heat insulation, thermal insulation, and resistance to flame can be secured.
[0042] The curable composition may additionally include necessary components in addition to the above components.
[0043] In one example, the curable composition may include a curing agent component. The type of the curing agent component is determined according to the curability of the polyorganosiloxane component and is not particularly limited, and an appropriate type may be selected.
[0044] For example, if the above polyorganosiloxane component is an addition-curing type, a polyorganosiloxane component (a second polyorganosiloxane component) can also be used as a curing agent component.
[0045] In such cases, as a curing agent component, a polyorganosiloxane component including, for example, the polyorganosiloxane of Chemical Formula 2 below may be used. Additionally, the polyorganosiloxane component that is the curing agent component may be referred to as the second polyorganosiloxane component for convenience.
[0046] [Chemical Formula 2]
[0047]
[0048] In Chemical Formula 2, R3 is independently hydrogen or an alkyl group, R4 is independently an alkyl group, an aryl group, or an alkyl halide group, p and q are independently numbers within the range of 0 to 150, and p+q is 1 or more.
[0049] The second polyorganosiloxane component above may be a product of a polymerization reaction to form the polyorganosiloxane of the above formula 2, and thus may be a component containing the same.
[0050] Accordingly, in one example, the second polyorganosiloxane component may have an average unit corresponding to the polyorganosiloxane of Formula 2.
[0051] In one example, the second polyorganosiloxane component may have an average unit of the following chemical formula 2-1.
[0052] [Chemical Formula 2-1]
[0053] (R3(R4)2SiO 1 / 2 ) 2 / (2+p+q) ((R4)2SiO 2 / 2 ) p / (2+p+q) (HR4SiO 2 / 2 ) q / (2+p+q)
[0054] In Chemical Formula 2-1, R3 and R4 are organic functional groups bonded to the silicon atoms of each siloxane unit, specifically R3 and R4 of Chemical Formula 2, respectively, p and q are each independently numbers within the range of 0 to 150, and p+q is 1 or more.
[0055] In Chemical Formula 2 or Chemical Formula 2-1, R3 can be a hydrogen atom in one example.
[0056] By applying the first and second polyorganosiloxane components together with the filler, a curable composition exhibiting physical properties suitable for the purpose of the present application can be provided.
[0057] The above curing agent component (the second polyorganosiloxane component) may be included in the curable composition in a ratio of 0.1 to 20 parts by weight relative to 100 parts by weight of the first polyorganosiloxane component. The above ratio may be 0.5 parts by weight or more, 1 part by weight or more, 1.5 parts by weight or more, 2 parts by weight or more, 2.5 parts by weight or more, 3 parts by weight or more, 3.5 parts by weight or more, 4 parts by weight or more, 4.5 parts by weight or more, 5 parts by weight or more, 5.5 parts by weight or more, 6 parts by weight or more, 6.5 parts by weight or more, 7 parts by weight or more, 7.5 parts by weight or more, 8 parts by weight or more, 8.5 parts by weight or more, 9 parts by weight or more, 9.5 parts by weight or more, or 10 parts by weight or more, or 18 parts by weight or less, 16 parts by weight or less, 14 parts by weight or less, 12 parts by weight or less, 10 parts by weight or less, 8 parts by weight or less, or 6 parts by weight or less.
[0058] In another example, when the above polyorganosiloxane component is of the condensation curing type, the above curing agent component may be a compound of the following chemical formula 3 or a component containing such a compound.
[0059] [Chemical Formula 3]
[0060]
[0061] In Chemical Formula 3, R3 to R6 are each independently hydrogen, an amino group, an acetoxy group, a hydroxyl group, an alkoxy group, a functional group of Chemical Formula 4 below, a functional group of Chemical Formula 5 below, or an alkyl group.
[0062] [Chemical Formula 4]
[0063]
[0064] In chemical formula 4, R7 is hydrogen, an alkyl group, an alkoxy group, an alkenyl group, an alkynyl group, or an aryl group.
[0065] [Chemical Formula 5]
[0066]
[0067] In Chemical Formula 5, R8 to R 10Each is independently hydrogen, an alkyl group, an alkoxy group, an alkenyl group, an alkynyl group, or an aryl group.
[0068] The structure of the compound of Chemical Formula 3 can be further controlled to form a suitable cured product.
[0069] For example, in the above formula 3, two or more or three of R3 to R6 may be an amino group, an acetoxy group, a hydroxyl group, an alkoxy group, or a functional group of the above formula 4 or a functional group of the above formula 5.
[0070] In addition, for example, R3 to R6 in the above formula 3, which are not the amino group, acetoxy group, hydroxyl group, alkoxy group, or the functional group of the above formula 4 or the functional group of the above formula 5, may be alkyl groups.
[0071] The compound of Chemical Formula 3 above may be included in the curable composition in a ratio of about 0.05 to 10 parts by weight relative to 100 parts by weight of the polyorganosiloxane component. The above ratio is, in other examples, 0.1 parts by weight or more, 0.15 parts by weight or more, 0.2 parts by weight or more, 0.25 parts by weight or more, 0.3 parts by weight or more, 0.35 parts by weight or more, 0.4 parts by weight or more, 0.45 parts by weight or more, 0.5 parts by weight or more, 0.55 parts by weight or more, 0.6 parts by weight or more, 0.65 parts by weight or more, 0.7 parts by weight or more, 0.75 parts by weight or more, 0.8 parts by weight or more, 0.85 parts by weight or more, 0.9 parts by weight or more, or 0.95 parts by weight or more, or 9.5 parts by weight or less, 9.0 parts by weight or less, 8.5 parts by weight or less, 8.0 parts by weight or less, 7.5 parts by weight or less, 7.0 parts by weight or less, 6.5 parts by weight or less, 6.0 parts by weight or less, 5.5 parts by weight or less, 5.0 parts by weight or less, 4.5 parts by weight It may be less than or equal to 4.0 parts by weight, less than or equal to 3.5 parts by weight, less than or equal to 3.0 parts by weight, less than or equal to 2.5 parts by weight, less than or equal to 2.0 parts by weight, less than or equal to 1.5 parts by weight, less than or equal to 1.0 parts by weight, less than or equal to 0.95 parts by weight, less than or equal to 0.9 parts by weight, less than or equal to 0.85 parts by weight, less than or equal to 0.8 parts by weight, less than or equal to 0.75 parts by weight, less than or equal to 0.7 parts by weight, less than or equal to 0.65 parts by weight, less than or equal to 0.6 parts by weight, or less than or equal to 0.55 parts by weight.
[0072] The curable composition may include additional components necessary for the above components. For example, the curable composition may include a catalyst for the reaction between the polyorganosiloxane component and the compound of Formula 2 (e.g., a platinum-based catalyst), a flame retardant, or other additives.
[0073] If necessary, the above-mentioned curable composition may be formulated such that the absolute value of K in Formula 1 below is within the range of 0.005 to 2.5. However, it is not essential to ensure that the absolute value of K in Formula 1 above is within the range of 0.005 to 2.5, and if the desired physical properties are obtained without the above control, the control of the K value may be unnecessary.
[0074] [Formula 1]
[0075] K = (ρ1-ρ2)×D 2 / μ
[0076] In Formula 1, ρ1 is the density of the polyorganosiloxane component, ρ2 is the density of the filler, D is the D50 particle size of the filler, and μ is the viscosity of the curable composition at 25°C.
[0077] The polyorganosiloxane component defining ρ1 of Formula 1 may be any polyorganosiloxane component included in the curable composition, or a polyorganosiloxane component excluding the curing agent component.
[0078] For example, in the case where the polyorganosiloxane component containing the curable polyorganosiloxane is of the condensation curing type and the curing agent component containing the polyorganosiloxane component and the compound of Formula 3 is included, ρ1 of Formula 1 may be the density of the polyorganosiloxane component.
[0079] For example, in the case where the polyorganosiloxane component containing the curable polyorganosiloxane is of the addition curing type, and the polyorganosiloxane component containing the curable polyorganosiloxane (first polyorganosiloxane component) and the polyorganosiloxane component as the curing agent (second polyorganosiloxane component) are included, ρ1 of Formula 1 may be the density of the mixture of the first and second polyorganosiloxane components, or the density of the first polyorganosiloxane component.
[0080] ρ1 in Formula 1 can be approximately 0.4 to 2 g / ml in one example.
[0081] The above density may be 0.45 g / ml or more, 0.5 g / ml or more, 0.55 g / ml or more, 0.6 g / ml or more, 0.65 g / ml or more, 0.7 g / ml or more, 0.75 g / ml or more, 0.8 g / ml or more, 0.85 g / ml or more, 0.9 g / ml or more, or 0.95 g / ml or more, or 1.8 g / ml or less, 1.6 g / ml or less, 1.4 g / ml or less, 1.2 g / ml or less, or 1.0 g / ml or less.
[0082] In Formula 1, ρ2 and D are as described in the above filler item.
[0083] Meanwhile, μ in Formula 1 is the viscosity of the curable composition at 25°C, and the range may be within the range of 500 to 80,000 mPa·s.The above viscosity is 550 mPa·s or more, 600 mPa·s or more, 650 mPa·s or more, 700 mPa·s or more, 750 mPa·s or more, 800 mPa·s or more, 850 mPa·s or more, 900 mPa·s or more, 950 mPa·s or more, 1000 mPa·s or more, 1500 mPa·s or more, 2000 mPa·s or more, 2500 mPa·s or more, 3000 mPa·s or more, 3500 mPa·s or more, 4000 mPa·s or more, 4500 mPa·s or more, 5000 mPa·s or more, 5500 mPa·s or more, 6000 mPa·s or more, 6500 mPa·s or more, 7000 mPa·s or more, in other examples 7500 mPa·s or more, 8000 mPa·s or more, 8500 mPa·s or more, 9000 mPa·s or more, 9500 mPa·s or more, 10000 mPa·s or more, 15000 mPa·s or more, 20000 mPa·s or more, 25000 mPa·s or more, 30000 mPa·s or more, 35000 mPa·s or more, 40000 mPa·s or more, 45000 mPa·s or more, 50000 mPa·s or more, or 55000 mPa·s or more, or 75000 mPa·s or less, 70000 mPa·s or less, 65000 mPa·s or less, 60000 mPa·s or less, 55000 mPa·s or less, 50000 mPa·s ≤, 45000 mPa·s ≤, 40000 mPa·s ≤, 35000 mPa·s ≤, 30000 mPa·s ≤, 25000 mPa·s ≤, 20000 mPa·s ≤, 15000 mPa·s ≤, 10000 mPa·s ≤, 9500 mPa·s ≤, 9000 mPa·s ≤, 8500 mPa·s ≤, 8000 mPa·s ≤, 7500 mPa·s ≤, 7000 mPa·s ≤, 6500 mPa·s ≤, 6000 mPa·s ≤, 5500 mPa·s ≤, 5000 mPa·s ≤, 4500 mPa·s ≤, 4000 mPa·s ≤, 3500 mPa·s ≤, It may be 3000 mPa·s or less, 2500 mPa·s or less, 2000 mPa·s or less, or 1500 mPa·s or less.
[0084] A curable composition or cured product containing the above components may have a density of about 0.4 to 5 g / ml.
[0085] The above density may be 0.45 g / ml or more, 0.5 g / ml or more, 0.55 g / ml or more, 0.6 g / ml or more, 0.65 g / ml or more, 0.7 g / ml or more, or 0.75 g / ml or more in other examples, or 4.5 g / ml or less, 4 g / ml or less, 3.5 g / ml or less, 3 g / ml or less, 2.5 g / ml or less, 2 g / ml or less, 1.5 g / ml or less, 1 g / ml or less, 0.95 g / ml or less, 0.9 g / ml or less, 0.85 g / ml or less, 0.8 g / ml or less, 0.75 g / ml or less, or about 0.7 g / ml or less.
[0086] A curable composition with desired physical properties can be provided at the above viscosity and / or density.
[0087] As described above, the curable composition can be used as a battery potting material in one example.
[0088] The present application also relates to a battery module to which the potting material is applied. Such a battery module can exhibit high output while being lightweight relative to its volume, and heat generated from battery cells, etc., is properly controlled, and problems such as chain ignition do not occur.
[0089] The battery module may, in one example, comprise a substrate; a plurality of battery cells disposed on the substrate; and the curable composition or the cured product covering at least a portion or all of the plurality of battery cells.
[0090] In the above structure, the curable composition or the cured product (potting material) may, in one example, cover the battery cells while in contact with the front surface of the plurality of battery cells (excluding the surface of the battery cell in contact with the substrate side) (structure of FIG. 1), or may be in contact only with the upper surface of the plurality of battery cells (structure of FIG. 2).
[0091] FIGS. 1 and 2 are schematic diagrams of the structure of a battery module as described above, and are drawings showing a structure including a substrate (10); a battery cell (20); and a potting material (30, the curable composition or the cured product thereof). The battery module may additionally include an adhesive material (40) for fixing the battery cell (20) to the substrate (10), and in one example, the adhesive material (40) may be configured to have thermal conductivity.
[0092] As long as the above-mentioned curable composition or the cured product is applied as a potting material, the specific configuration of the battery module, for example, the type of battery cell, substrate, and / or adhesive material, is not particularly limited, and known materials may be applied.
[0093] For example, known pouch-type, prismatic, or cylindrical battery cells may be used as the battery cells, and known materials may also be used as the substrate or adhesive material.
[0094] The method of manufacturing the above battery module is not particularly limited, and, for example, it can be formed by pouring the curable composition onto the upper portion of a plurality of battery cells formed on a substrate and, if necessary, curing it.
[0095] Since the curable composition of the present application has appropriate viscosity and thixotropy, it can efficiently fill the space between very closely spaced battery cells and, after forming a potting material, can exhibit the desired thermal insulation and heat shielding properties. Effects of the invention
[0096] The present application provides a curable composition, and in one example, said curable composition may be used as a potting material when constructing a battery module or battery pack. The potting material may be a material that covers and contacts at least some or all of a plurality of unit battery cells within a battery module or battery pack. The present application provides a curable composition that possesses excellent thermal insulation and heat shielding properties and exhibits resistance to flame, thereby controlling the heat generated in the battery cells of the battery module or pack and preventing chain ignition, etc., when applied as a potting material. The present application also provides a curable composition that has excellent potting efficiency by controlling viscosity or thixotropy to an appropriate level before curing, and forms a stable potting structure without the generation of unnecessary bubbles after curing. The present application provides a curable composition that exhibits low density after curing, thereby providing a high-output battery module or pack that is lightweight relative to its volume. The present application also provides a curable composition that has excellent required physical properties, including insulation properties. Brief explanation of the drawing
[0097] FIGS. 1 and 2 are schematic diagrams of an exemplary battery module of the present application. Figure 3 is a diagram showing the arrangement of battery cells, measuring the charging time, chain ignition test, and the temperature of adjacent battery cells. Specific details for implementing the invention
[0098] The present application will be specifically described through the following examples, but the scope of the present application is not limited by the following examples.
[0100] 1. Viscosity measurement
[0101] The viscosity of the polyorganosiloxane component and the curable composition was measured at 25°C using a Brookfield Viscometer (LV Type). Spindle #63 or #64 was used for measurement, and the measurement was performed at 10 rpm.
[0103] 2. Density measurement
[0104] The density of the polyorganosiloxane component, curable composition, or filler was measured at 25°C according to ASTM D792.
[0106] 3. Evaluation of filling time
[0107] Cylindrical battery cells of 21700 specifications (21mm × 70mm) were arranged in a honeycomb structure as shown in Fig. 3 (a gap of 1 mm between battery cells). A thermocouple was attached to the battery cells and fixed to a lower jig. Then, 700 mL of a curable composition was evenly poured over the top of the fixed battery cells, and the time taken for the gap between the battery cells to be completely filled with the curable composition was measured. If the curable composition was completely filled within 5 minutes, it was evaluated as PASS, and if it was filled after 5 minutes or not filled at all, it was evaluated as NG.
[0109] 4. Chain Ignition Test
[0110] As in the charging time evaluation, after potting the battery cells arranged in the configuration of Fig. 3 with a potting material, battery cell No. 7 of Fig. 3 was charged to 100% for 30 minutes and then overcharged for 5 minutes to induce ignition. If only battery cell No. 7 ignited after the above induction, it was evaluated as PASS, and if the ignition spread to other battery cells, it was evaluated as NG.
[0112] 5. Flame Retardancy Evaluation
[0113] After curing the curable composition of the example or comparative example into a film with a width, length, and thickness of 125 mm, 13 mm, and 3 mm, respectively, the flame was ignited for 10 seconds using a torch with a 20 mm flame, and the burning time was measured. If the time taken to remove the flame was less than 10 seconds, it was evaluated as PASS, and if it exceeded 10 seconds, it was evaluated as NG.
[0115] 6. Evaluation of Phase Separation Characteristics
[0116] The curable composition of the example or comparative example was placed in a 50 ml vial, and after leaving it for 30 minutes, the occurrence of phase separation was observed. If no phase separation occurred, it was evaluated as PASS, and if it occurred, it was evaluated as NG.
[0118] 7. Filler D50 particle size
[0119] The D50 particle size of the filler was measured using a Marvern MASTERSIZER 3000 instrument in accordance with ISO-13320. Ethanol was used as the solvent for the measurement. The principle of D50 particle size measurement is as follows. First, an incident laser is scattered by particles dispersed in the solvent; the intensity and directionality of the scattered laser vary depending on the particle size. By analyzing these values using Mie theory and converting them into the diameter of a sphere with the same volume as the dispersed particles to obtain a distribution map, the particle size can be evaluated by calculating the D50 value, which is the median of the distribution map.
[0121] Example 1.
[0122] A polyorganosiloxane component was prepared by mixing a polyorganosiloxane component containing a curable polyorganosiloxane (Gelest’s DMS-V22) (A), a curing agent component polyorganosiloxane component (Gelest’s DMS-H21) (B), and a catalyst component (Alfa Chemistry, platinum bis(1,3-bis(h2-ethenyl)-1,1,3,3-tetramethyldisiloxane) (D). The mixing ratio of the components was controlled to 100:5:0.1 (A:B:C), and mixing was performed at 25°C for 1 hour at 300 rpm.
[0123] The viscosity of the above polyorganosiloxane component at 25°C was approximately 200 mPa·s.
[0124] Next, a filler (3M, Glassbubble K15) was mixed into the above mixture and stirred for 2 hours at 500 rpm, and then further mixed for 20 minutes at 50 rpm in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 7.6 wt%. The density of the polyorganosiloxane component (ρ1 of Formula 1, unit: g / ml), the density of the filler (ρ2 of Formula 1, unit: g / ml), the D50 particle size of the filler (D of Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ of Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0126] Example 2.
[0127] A polyorganosiloxane component was prepared by mixing a polyorganosiloxane component containing a curable polyorganosiloxane (Gelest’s DMS-V22) (A), a curing agent component polyorganosiloxane component (Gelest’s DMS-H21) (B), and a catalyst component (Alfa Chemistry, platinum bis(1,3-bis(h2-ethenyl)-1,1,3,3-tetramethyldisiloxane) (D). The mixing ratio of the components was controlled to 100:5:0.1 (A:B:C), and mixing was performed at 25°C for 1 hour at 300 rpm.
[0128] The viscosity of the above polyorganosiloxane component at 25°C was approximately 200 mPa·s.
[0129] Next, a filler (3M, Glassbubble S38) was mixed into the above mixture and stirred for 2 hours at 500 rpm, and then further mixed for 20 minutes at 50 rpm in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 31 wt%. The density of the polyorganosiloxane component (ρ1 of Formula 1, unit: g / ml), the density of the filler (ρ2 of Formula 1, unit: g / ml), the D50 particle size of the filler (D of Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ of Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0131] Example 3.
[0132] A polyorganosiloxane component was prepared by mixing a polyorganosiloxane component containing a curable polyorganosiloxane (Gelest’s DMS-V22) (A), a curing agent component polyorganosiloxane component (Gelest’s DMS-H21) (B), and a catalyst component (Alfa Chemistry, platinum bis(1,3-bis(h2-ethenyl)-1,1,3,3-tetramethyldisiloxane) (D). The mixing ratio of the components was controlled to 100:5:0.1 (A:B:C), and mixing was performed at 25°C for 1 hour at 300 rpm.
[0133] The viscosity of the above polyorganosiloxane component at 25°C was approximately 200 mPa·s.
[0134] Next, a filler (3M, Glassbubble S38) was mixed into the above mixture and stirred for 2 hours at 500 rpm, and then further mixed for 20 minutes at 50 rpm in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 27.5 wt%. The density of the polyorganosiloxane component (ρ1 of Formula 1, unit: g / ml), the density of the filler (ρ2 of Formula 1, unit: g / ml), the D50 particle size of the filler (D of Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ of Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0136] Example 4.
[0137] A polyorganosiloxane component was prepared by mixing a polyorganosiloxane component containing a curable polyorganosiloxane (Gelest’s DMS-V22) (A), a curing agent component polyorganosiloxane component (Gelest’s DMS-H21) (B), and a catalyst component (Alfa Chemistry, platinum bis(1,3-bis(h2-ethenyl)-1,1,3,3-tetramethyldisiloxane) (D). The mixing ratio of the components was controlled to 100:5:0.1 (A:B:C), and mixing was performed at 25°C for 1 hour at 300 rpm.
[0138] The viscosity of the above polyorganosiloxane component at 25°C was approximately 200 mPa·s.
[0139] Next, a filler (Al(OH)3, Aldrich) was mixed into the above mixture and stirred for 2 hours at 500 rpm, and then further mixed for 20 minutes at 50 rpm in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 91.8 wt%. The density of the polyorganosiloxane component (ρ1 of Formula 1, unit: g / ml), the density of the filler (ρ2 of Formula 1, unit: g / ml), the D50 particle size of the filler (D of Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ of Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0141] Example 5.
[0142] A polyorganosiloxane component was prepared by mixing a polyorganosiloxane component containing a curable polyorganosiloxane (Gelest’s DMS-V25) (A), a curing agent component, a polyorganosiloxane component (Gelest’s DMS-H21) (B), and a catalyst component (Alfa Chemistry, platinum bis(1,3-bis(h2-ethenyl)-1,1,3,3-tetramethyldisiloxane) (D). The mixing ratio of the components was controlled to 100:5:0.1 (A:B:C), and mixing was performed at 25°C for 1 hour at 300 rpm.
[0143] The viscosity of the above polyorganosiloxane component at 25°C was approximately 500 mPa·s.
[0144] Next, a filler (cenosphere filler, Henan Daye Metallurgy Casting Material) was mixed into the above mixture and stirred for 2 hours at 500 rpm, and then further mixed for 20 minutes at 50 rpm in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 28.57 wt%. The density of the polyorganosiloxane component (ρ1 in Formula 1, unit: g / ml), the density of the filler (ρ2 in Formula 1, unit: g / ml), the D50 particle size of the filler (D in Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ in Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0146] Comparative Example 1.
[0147] A polyorganosiloxane component was prepared by mixing a polyorganosiloxane component containing a curable polyorganosiloxane (Gelest’s DMS-V22) (A), a curing agent component polyorganosiloxane component (Gelest’s DMS-H21) (B), and a catalyst component (Alfa Chemistry, platinum bis(1,3-bis(h2-ethenyl)-1,1,3,3-tetramethyldisiloxane) (D). The mixing ratio of the components was controlled to 100:5:0.1 (A:B:C), and mixing was performed at 25°C for 1 hour at 300 rpm.
[0148] The viscosity of the above polyorganosiloxane component at 25°C was approximately 200 mPa·s.
[0149] Next, a filler (Al2O3, Aldrich) was mixed into the above mixture and stirred for 2 hours at 500 rpm, and then further mixed for 20 minutes at 50 rpm in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 268 wt%. The density of the polyorganosiloxane component (ρ1 of Formula 1, unit: g / ml), the density of the filler (ρ2 of Formula 1, unit: g / ml), the D50 particle size of the filler (D of Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ of Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0151] Comparative Example 2.
[0152] A polyorganosiloxane component was prepared by mixing a polyorganosiloxane component containing a curable polyorganosiloxane (Gelest’s DMS-V22) (A), a curing agent component polyorganosiloxane component (Gelest’s DMS-H21) (B), and a catalyst component (Alfa Chemistry, platinum bis(1,3-bis(h2-ethenyl)-1,1,3,3-tetramethyldisiloxane) (D). The mixing ratio of the components was controlled to 100:5:0.1 (A:B:C), and mixing was performed at 25°C for 1 hour at 300 rpm.
[0153] The viscosity of the above polyorganosiloxane component at 25°C was approximately 200 mPa·s.
[0154] Next, a filler (3M, Glassbubble K15 polarized to a 120 μm mesh) was mixed into the above mixture and stirred for 2 hours at 500 rpm, and then further mixed for 20 minutes at 50 rpm in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 80 wt%. The density of the polyorganosiloxane component (ρ1 of Formula 1, unit: g / ml), the density of the filler (ρ2 of Formula 1, unit: g / ml), the D50 particle size of the filler (D of Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ of Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0156] Comparative Example 3.
[0157] A polyorganosiloxane component was prepared by mixing a polyorganosiloxane component containing a curable polyorganosiloxane (Gelest’s DMS-V22) (A), a curing agent component polyorganosiloxane component (Gelest’s DMS-H21) (B), and a catalyst component (Alfa Chemistry, platinum bis(1,3-bis(h2-ethenyl)-1,1,3,3-tetramethyldisiloxane) (D). The mixing ratio of the components was controlled to 100:5:0.1 (A:B:C), and mixing was performed at 25°C for 1 hour at 300 rpm.
[0158] The viscosity of the above polyorganosiloxane component at 25°C was approximately 200 mPa·s.
[0159] Next, a filler (Al(OH)3, Aldrich) was mixed into the above mixture and stirred for 2 hours at 500 rpm, and then further mixed for 20 minutes at 50 rpm in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 400 wt%. The density of the polyorganosiloxane component (ρ1 of Formula 1, unit: g / ml), the density of the filler (ρ2 of Formula 1, unit: g / ml), the D50 particle size of the filler (D of Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ of Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0161] Comparative Example 4.
[0162] A curable composition was prepared by mixing a filler into a curable urethane composition (LORD, Circalok 6412).
[0163] The viscosity of the above-mentioned curable urethane composition at 25°C was approximately 700 mPa·s.
[0164] The above curable urethane composition and the filler (cenosphere filler, Henan Daye Metallurgy Casting Material) were stirred at 500 rpm for 2 hours, and then further mixed at 50 rpm for 20 minutes in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 80 wt%. The density of the polyorganosiloxane component (ρ1 in Formula 1, unit: g / ml), the density of the filler (ρ2 in Formula 1, unit: g / ml), the D50 particle size of the filler (D in Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ in Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0166] Comparative Example 5.
[0167] A polyorganosiloxane component was prepared by mixing a polyorganosiloxane component containing a curable polyorganosiloxane (Gelest’s DMS-V22) (A), a curing agent component polyorganosiloxane component (Gelest’s DMS-H21) (B), and a catalyst component (Alfa Chemistry, platinum bis(1,3-bis(h2-ethenyl)-1,1,3,3-tetramethyldisiloxane) (D). The mixing ratio of the components was controlled to 100:5:0.1 (A:B:C), and mixing was performed at 25°C for 1 hour at 300 rpm.
[0168] The viscosity of the above polyorganosiloxane component at 25°C was about 20 mPa·s.
[0169] Next, a filler (Al2O3, Aldrich) was mixed into the above mixture and stirred for 2 hours at 500 rpm, and then further mixed for 20 minutes at 50 rpm in a vacuum atmosphere to prepare a curable composition. The content of the filler in the above curable composition was approximately 76 wt%. The density of the polyorganosiloxane component (ρ1 of Formula 1, unit: g / ml), the density of the filler (ρ2 of Formula 1, unit: g / ml), the D50 particle size of the filler (D of Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ of Formula 1, unit: mPa·s) in the above curable composition are summarized in Table 1 below.
[0171] The density of the polyorganosiloxane component (ρ1 of Formula 1, unit: g / ml) (density of the urethane composition in the case of Comparative Example 4), the density of the filler (ρ2 of Formula 1, unit: g / ml), the D50 particle size of the filler (D of Formula 1, unit: μm), and the viscosity of the curable composition at 25°C (μ of Formula 1, unit: mPa·s) in the curable compositions of the above examples and comparative examples are summarized in Table 1 below.
[0172] Density (ρ1) of polyorganosiloxane components (g / ml) Filler density (ρ2) (g / ml) D50 particle size (D) (μm) of the filler 25 viscosity (μ) (mPa·s) of the curable composition Examples 1 0.98 0.15 60 2800 2 0.98 0.38 40 3700 3 0.98 0.38 40 1200 4 0.98 2.42 10 17000 5 0.98 0.35 90 5800 Comparative example 1 0.98 3.76 70 3200 2 0.98 0.15 120 4700 3 0.98 2.35 120 120000 4 0.98 0.35 90 6000 5 0.98 3.76 1 350
[0173] The evaluation results for the curable compositions of the above examples and comparative examples are summarized in Table 2 below.
[0174] Examples Comparative example 1 2 3 4 5 1 2 3 4 5 Cured material density (g / ml) 0.7 0.71 0.96 1.7 0.7 2.12 0.61 1.83 0.7 1.44 flame retardant PASS PASS PASS PASS PASS PASS PASS PASS NG NG Phase separation PASS PASS PASS PASS PASS NG NG PASS PASS NG Filling speed PASS PASS PASS PASS PASS PASS PASS NG PASS PASS chain reaction PASS PASS PASS PASS PASS PASS PASS NG PASS NG
Claims
Claim 1 A curable composition comprising a polyorganosiloxane component including a curable polyorganosiloxane; and a filler, wherein the polyorganosiloxane component has a viscosity at 25°C of 100 mPa·s or more and 4000 mPa·s or less, the viscosity at 25°C of the curable composition is within the range of 1000 to 15000 mPa·s, and the absolute value of K in Formula 1 below is within the range of greater than 0.16 to 2.5 or less: [Formula 1] K = (ρ1-ρ2)×D 2 In Formula 1, ρ1 is the density of the polyorganosiloxane component (unit: g / ml), ρ2 is the density of the filler (unit: g / ml), D is the D50 particle size of the filler (unit: μm), and μ is the viscosity of the curable composition at 25°C (unit: mPa·s). Claim 2 delete Claim 3 delete Claim 4 In claim 1, the curable polyorganosiloxane is a curable composition represented by the following chemical formula 1: [Chemical Formula 1] In Chemical Formula 1, R1 is each independently an alkyl group, an alkenyl group, an aryl group, or an alkyl halide group, R2 is a hydroxyl group, an alkoxy group, an alkenyl group, or an alkynyl group, and m is a number in the range of 10 to 350. Claim 5 In claim 1, the filler is a hollow filler, a curable composition. Claim 6 In claim 1, the filler is a curable composition having a D50 particle size in the range of 10 μm to 100 μm. Claim 7 In claim 1, the filler is a curable composition having a density in the range of 0.05 to 1 g / ml. Claim 8 A curable composition according to claim 1, wherein the filler is a soda-lime filler, a soda-lime borosilicate filler, a cenosphere filler, or a silica filler. Claim 9 A curable composition according to claim 1, wherein the filler is included in a ratio of 3 to 150 parts by weight per 100 parts by weight of a polyorganosiloxane component. Claim 10 A curable composition according to claim 1, further comprising a curing agent component. Claim 11 In claim 10, the curable composition wherein the curing agent component is a polyorganosiloxane component comprising a polyorganosiloxane of the following chemical formula 2: [Chemical Formula 2] In Chemical Formula 2, R3 is hydrogen, R4 is each independently an alkyl group, an aryl group, or an alkyl halide group, p and q are each independently numbers within the range of 0 to 150, and p+q is 1 or more. Claim 12 A curable composition according to claim 11, wherein the curing agent component is included in a ratio of 0.1 to 20 parts by weight per 100 parts by weight of the polyorganosiloxane component. Claim 13 In claim 10, the curing agent component is a curable composition comprising a compound of the following chemical formula 3: [Chemical Formula 3] In Chemical Formula 3, R3 to R6 are each independently hydrogen, an amino group, an acetoxy group, a hydroxyl group, an alkoxy group, a functional group of Chemical Formula 4 below, a functional group of Chemical Formula 5 below, or an alkyl group: [Chemical Formula 4] In Chemical Formula 4, R7 is hydrogen, an alkyl group, an alkoxy group, an alkenyl group, an alkynyl group, or an aryl group: [Chemical Formula 5] In Chemical Formula 5, R8 to R 10 Each is independently hydrogen, an alkyl group, an alkoxy group, an alkenyl group, an alkynyl group, or an aryl group. Claim 14 A curable composition according to claim 13, wherein the compound of Formula 3 is included in a ratio of 0.5 to 10 parts by weight per 100 parts by weight of the polyorganosiloxane component. Claim 15 delete Claim 16 A curable composition according to claim 1, wherein the density is within the range of 0.4 to 1 g / ml. Claim 17 A battery module comprising: a substrate; a plurality of battery cells disposed on the substrate; and a curable composition of claim 1 or a cured product thereof covering at least a portion of the plurality of battery cells. Claim 18 In claim 17, a battery module in which the battery cell is a pouch-type, prismatic, or cylindrical battery cell.
Citation Information
Patent Citations
Secondary battery pack with improved thermal management
KR1020190132631A
Binder composition and use thereof
WO2019145352A1